An aperture of 21 cm telescope with polarized coaxial for satellite laser ranging - Long, Mingliang; Deng, Huarong; Zhang, Haifeng; Tan, Kai; Lin, Hai sheng; Wu, Zhibo; Zhang, Zhongping (Frontiers in Physics, 2023)
With the development of aerospace and space scientific research, satellite laser ranging (SLR) has put forward higher requirements for response speed, data density, and measurement accuracy.In coaxial common optical path laser ranging, the emitted laser and the received laser echoes pass through the same optical system. Due to the reversibility of the optical path, the laser emission, monitoring and laser echoes’ optical path all pass through the same optical system structure, and the response speed and ranging ability of the laser ranging system have been greatly improved.Based on the SLR system of the Shanghai Astronomical Observatory (SHAO), the laser transmitting telescope with an aperture of 21 cm was used to build a polarization coaxial SLR. It uses a picosecond pulsed laser with a pulse repetition frequency of 2 kHz and a single pulse energy of 2 mJ, and also a 4f system was applied to shrink the laser echo beam and filter out noise, the measurement of low-earth orbit and long-distance high-orbit satellites was realized,the ranging accuracy is 2 cm. As far as we know, this is currently the smallest aperture telescopes for SLR in all world, which is conducive to the miniaturization and integrated development of SLR systems.